Model Checking Communicating Processes: Run Graphs, Graph Grammars, and MSO - Heußner, Alexander (Electronic Communications of the EASST, 2012)
The formal model of recursive communicating processes (RCPS) is important in practice but does not allows to derive decidability results for model checking questions easily. We focus a partial order representation of RCPS’s execution by graphs—so called run graphs, and suggest an underapproximative verification approach based on a bounded-treewidth requirement. This allows to directly derive positive decidability results for MSO model checking (seen as partial order logic on run graphs) based on a context-freeness argument for restricted classes run graph.